The Correlation Between the Use of YouTube and Speaking Ability on English Department Students of Riau University - Annisa Suandy; Novitri Novitri; Masyhur Masyhur (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out the correlation between the use of YouTube and speaking ability on English Department students of Riau University. The research design was descriptive correlational that focused on the quantitative approach. The population of the research is the fourth semester of the English department with 76 students involved as the research samples. To collect the data, the researcher used two research instruments; a questionnaire and a test. The questionnaire is to gain the data of the students’ use of YouTube while the test is for the data of the students’ speaking ability. The analysis of the data was carried out using IBM SPSS Statistics 25. The findings revealed that the mean score of the students’ social use of YouTube is 75.58, interpreted as ‘average’, whereas the mean score of the students’ speaking ability is 69.99, interpreted as ‘good’. Then this research discovered the correlation coefficient between the two variables is 0.471, and following the classification of correlation by Sugiyono (2009), this number denotes a ‘moderate’ and ‘positive’ correlation. Also, the determinant coefficient is 0.2218, indicating that the students’ use of YouTube has 22% influence on their speaking ability, leaving the other 78% to other factors, such as cognitive ones (conceptualization, formulation, and articulation), lingustic ones (pronunciation, grammar, and vocabulary), and affective ones (self-control and anxiety). Having found these findings, it can be confirmed that the use of YouTube can influence students’ English speaking ability very well if they start using it wisely.